ANALISIS YURIDIS PERLINDUNGAN KONSUMEN DALAM PRODUK GADAI EMAS (RAHN EMAS) PADA BANK SYARIAH INDONESIA BINJAI: PERSPEKTIF HUKUM EKONOMI SYARIAH DAN REGULASI NASIONAL - Firmansah, Ilham; Abdullah, Budi; Rahman Purba, Abdur (Izdihar: Jurnal Ekonomi Syariah, 2026)
This study aims to analyze consumer legal protection in gold pawn (rahn emas) products at Bank Syariah Indonesia (BSI) Binjai from the perspective of Islamic economic law. The method used is a normative juridical approach by analyzing laws and regulations, DSN-MUI fatwas, and related legal documents, without involving direct interviews. The results of the study indicate that although the rahn emas product has fulfilled formal legal aspects, there are still weaknesses in information transparency, collateral valuation, and contract (akad) education for customers. Information asymmetry and the lack of dispute resolution mechanisms show that legal protection has not fully reflected the principles of justice and public welfare (maslahah) in Islamic economic law. This study recommends strengthening internal regulations, improving consumer education, and implementing sharia-based dispute resolution mechanisms so that consumer legal protection can operate optimally. Keywords: Legal protection, rahn emas, consumer, Bank Syariah Indonesia, Islamic economic law